Financial Sector’s Cybersecurity : Regulations and Supervision - World Bank Group (World Bank, Washington, DC, 2018)
The Financial Sector’s Cybersecurity: Regulation and Supervision identifies prevalent concepts and practices and presents them in a way for financial sector authorities to consider and apply to their respective jurisdictions. Starting with the debate of whether cyber-specific regulations are necessary, the Paper goes on to discuss the essential coordination between financial sector authorities and other state agencies in dealing with cyber risk. It then moves on to the topic “taxonomies” as we all need to have a common language when speaking about cybersecurity to avoid any misunderstanding. Next sections discuss the issue of reiterating, or in some cases redefining, the responsibilities of the Board, Senior Management, and the Information Security Officer, specifically in Dealing with cybersecurity. Next, a prominent feature in many supervisory/regulatory practices is the role of incident response and recovery, as well as requirements of tests and simulations. Lastly, the paper covers the managing of outsourcing risk.